2016
DOI: 10.1007/s10648-016-9376-0
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Reminiscing in Early Childhood Settings and Links to Sustained Shared Thinking

Abstract: The importance of parent-child reminiscing for young children's social and cognitive development has been well established, but despite the increasing numbers of children attending formal early childhood settings such as nurseries and preschools, there has been surprisingly little research exploring educator-child reminiscing in these contexts. Furthermore, existing research into educator-child interaction in the early years has focused on the identification and categorization of explicit learning episodes, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…According to the philosopher M. Bakhtin, the derivative of this sociocultural phenomenon is the meaning (Bakhtin, 1986). The importance of dialogue for the development of consciousness and speech was studied by the philosopher M. Mamardashvili, who showed that the consciousness of each person develops within a cultural whole, in which the experience of the activity, communication and world perception crystallizes (Mamardashvili, 1990;Neale, Pino-Pasternak, 2017). O. Ushakova demonstrated the important role of speech in the children's familiarization with the environment and setting up the system of connections with it in the process of the language personality formation (Ushakova, 2018; Rockestein, 2015).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the philosopher M. Bakhtin, the derivative of this sociocultural phenomenon is the meaning (Bakhtin, 1986). The importance of dialogue for the development of consciousness and speech was studied by the philosopher M. Mamardashvili, who showed that the consciousness of each person develops within a cultural whole, in which the experience of the activity, communication and world perception crystallizes (Mamardashvili, 1990;Neale, Pino-Pasternak, 2017). O. Ushakova demonstrated the important role of speech in the children's familiarization with the environment and setting up the system of connections with it in the process of the language personality formation (Ushakova, 2018; Rockestein, 2015).…”
Section: Problem Statementmentioning
confidence: 99%
“…The perception by teachers of their role as emotional socializers is important as well (Zinsser, Shewark, Denham, Curby, 2014), especially for young children when the emotionality, content and meaning of adult language play a major role in developing consciousness (Neale, Pino-Pasternak, 2017).…”
Section: Problem Statementmentioning
confidence: 99%
“…For example, global measures of maternal responsiveness have been linked with children's effortful control (Kochanska et al 2000;Kochanska et al 2008;Kochanska and Aksan 2004;Vallotton 2009). To really understand the social mechanisms that facilitate developmental change it is necessary to look at behaviour at the micro-level, on an utterance-by-utterance basis (Neale and Pino-Pasternak 2016). In this regard, micro-level codes can begin to address questions about mechanisms that macro-level coding cannot address.…”
mentioning
confidence: 99%
“…In addition, we were concerned to see if capturing maternal scaffolding at a more nuanced level would result in the detection of continuity in scaffolding behaviour over time. However, there are more advantages to be derived from the level of detail micro-coding provides (for examples, see Neale and Pino-Pasternak 2016).…”
mentioning
confidence: 99%
“…A study of the how, through a fine-grained investigation of interactions, can provide the specific pedagogical practices related to high quality (Neale & Pino-Pasternak, 2016). For example, studies identify the macro perspective of "warm interactive relationships" (Sylva, Melhuish, Sammons, Siraj-Blatchford, & Taggart, 2004a, p. 1) as one effective practice but they do not provide us with the fine-grained details,…”
Section: Thank You To the Transcript Analysis Group (Tag)mentioning
confidence: 99%